First description of a new cryptic species, Simulium vanluni from Peninsular Malaysia: An integrated morpho-taxonomical and genetic approach for naming cryptic species in the family Simuliidae - Ya'cob, Zubaidah; Takaoka, Hiroyuki; Low, Van Lun; Sofian-Azirun, Mohd (Elsevier, 2017)
In recent decades, the numbers of cryptic taxa have increased significantly with current progress in DNA barcoding, yet, most of these cryptic taxa have not been formally named and recognized as valid species. To address this issue, we provide a guide for applying the procedure of describing new cryptic species in the family Simuliidae. Simulium (Simulium) vanluni from Pahang, Peninsular Malaysia, previously treated as S. nobile De Meijere, is described as a new species by using an integrated morpho-taxonomical and genetic approach. This new species is morphologically identical to S. nobile from Java and S. kiuliense Smart & Clifford from Borneo, but their distinctiveness is supported by an expanded multigene phylogeny analysis.